Quality Of Physical Properties Chemical Liquid Organic Fertilizer from Tofu Liquid Waste With Banana Hump Mole Decomposer - Dwi Probowati Sulistyani; A. Napoleon; Bakri Bakri; Warsito Warsito (Program Pascasarjana Universitas Sriwijaya, 2023)
Liquid organic fertilizer is a fertilizer that is available in liquid form, liquid organic fertilizer can be interpreted as a fertilizer that is made naturally through a fermentation process so as to produce a solution of decay from plant residues. Liquid organic fertilizer is better to use because it is free from chemicals and has a good impact on health. The purpose of this research is to study the manufacturing technique and to determine the physical and chemical properties of liquid organic fertilizer from tofu liquid waste with banana hump mole decomposer. The research method is experimental. This research was conducted at the compost house and the Laboratory of Chemistry, Biology and Soil Fertility, Department of Soil Science, Faculty of Agriculture, Sriwijaya Indralaya University, Ogan Ilir. This activity was carried out in May - June 2022. The results obtained are the quality of the physical properties of liquid organic fertilizer from tofu liquid waste with banana hump moles with an average temperature of 26 to 29 degrees, yellow (8/8) 10YR color, characteristic sour smell, and TSS around 5132 – 5879 mg/liter. The quality of the chemical properties of liquid organic fertilizers is the average pH 3.62 – 3.72: N 7.98 – 8.22%, P 0.002%, K 0.03%